The Insurance Hypothesis and Market Prices. - Menon, Krishnagopal; Williams, David D. (The Accounting Review, 1994)
Examines the effect Laventhol & Horwath's (L&H) disclosure of their auditor's bankruptcy and the appointment of a successor auditor on the company's stock prices. Insurance hypothesis; Investors' assignment of a value to the right to recover investment losses from the auditor; Adverse effect of bankruptcy disclosure on market prices of L&H clients.